Virtual Reality Technology in Nursing Professional Skills Training: Bibliometric Analysis - Chengang Hong; Liping Wang (JMIR Publications, 2023)
BackgroundNursing professional skills training has undergone significant transformation due to the exponential growth of computer and medical technology. The innovative use of virtual reality (VR) in nursing education has emerged as a cutting-edge technical support technique that has gained attention as a highly effective method for improving nurse training quality. ObjectiveThis study aims to review the current status of VR technology in nursing professional skills training, research hotspots, and emerging trends in the last 15 years. MethodsThe Web of Science Core Collection database was used to search for literature on VR technology in nursing professional skills training covering the period from 2006 to 2022. Biblioshiny (K-Synth Srl) was used to import and convert the records to Bibliometrix (K-Synth Srl) for analysis, and R (R Core Team) was used for descriptive bibliometric analysis. VOSviewer (Leiden University) was used to cluster co-occurring keywords, and Scimago Graphica (version 1.0.16; Scimago Lab) was used to generate a geographical visualization of published countries and regions. ResultsA total of 1073 papers were analyzed, indicating a surge in research on the application of VR in nursing professional skills training in recent years, as evidenced by a positive trend in annual publication of relevant literature. The majority of studies were from the United States (n=340) and Canada (n=107), and Margaret Verkuyl was the most prolific author, leading the way with 9 publications. Furthermore, "Computerized Virtual Patients in Health Professions Education: a Systematic Review and Meta-Analysis" was the most frequently cited reference. Keywords such as education, simulation, skills, students, and care were most commonly used by researchers. ConclusionsThe bibliometric analysis provides a comprehensive overview of the use of VR in nursing professional skills training, indicating that VR-based training is an effective means of improving the skills and competencies of nursing students and professionals alike. The COVID-19 pandemic has reinforced the importance of developing VR-based distance education, despite challenges such as integrating virtual and real-world training and mitigating safety risks.